Routine use of intracardiac echocardiography for atrial flutter ablation is associated with reduced fluoroscopy time, but not with a reduction of radiofrequency energy delivery time - Herman, Dalibor; Osmancik, Pavel; Zdarska, Jana; Prochazkova, Radka (Journal of atrial fibrillation, 2017)
Background: The ablation of cavotricuspid-isthmus (CTI) atrial flutter (AFL) dependent atrial flutter could be difficult in patients with complex anatomy of the CTI.The aim of the study was to assess whether the use of intracardiac echocardiography (ICE) was associated with less fluoroscopy time and faster ablations of cavotricuspid isthmus dependent atrial flutter (CTI-AFL). Methods: Patients with an indication for an ablation of a CTI-AFL were enrolled. Patients in which ablation of a CTI-AFLas part of an atrial fibrillation ablation were not included. Randomization was done using the envelope method. Standard techniques (i.e., coronary sinus, 20-polar halo catheter, and an ablation catheter), and criteria of success (bidirectional block through the CTI) were used. In patients randomized to the ablation with ICE, a 10F AcuNav ICE probe (Siemens, Germany)was used. Results: Seventy-nine patients were enrolled; 40 were randomized to ablation with ICE and 39 without ICE. The X-ray exposure was shorter (3.29±2.6 vs. 5.94±3.43 min, p<0.001) and total X-ray dose was reduced (3.30±1.98 vs. 6.68±5.25 Gy.cm2, p<0.001) in the ICE group. However, the total RF energy ablation time was not different between groups (ICE group: 604.56±380.46sec vs. 585.82±373.39 sec, p=0.8). The procedure duration was slightly longer in the ICE group (82.0±20.8 vs. 72.1±19.0 min, p=0.03). Procedural success was 100% (40/40) in the ICE group and 95% (37/39) in the control group. Two control patients required crossover to ICE at a prespecified point to achieve bidirectional block. There were two femoral hematomas in the ICE group and one in the control group. Conclusion: The use of ICE for atrial flutter ablation is associated with less fluoroscopy time and improved ability to achieve bidirectional block compared to traditional conventional flutter ablation methods. However, it is not asoociated with reduced ablation time or overall procedure duration.